Synchronous colorectal cancer: a case report - Manalu, Ester Puti Andyni; Petrus, Gunadi (International Surgery Journal, 2023)
Synchronous colorectal cancer (CRCs) refers to more than 1 primary CRCs detected in a single patient simultaneously or within 6 months of the initial diagnosis. A 76-year-old men presented with persistent constipation since 1 month ago. Abdominal computed tomography (CT) showed an irregular mass in the right lower middle abdomen. Intraoperatively, the synchronous CRCs was found, therefore a subtotal colectomy was performed and the diagnosis was confirmed by histopathological examination. Synchronous CRCs is relatively rare. The CT can detect tumor, node, and metastasis (TNM) staging of colon cancer. Extensive resection was performed taking into account the patients preferences, number and location of tumors and postoperative plan. Surgeons should be familiar with all standard colorectal tumor surgical procedures, to avoid technical difficulties when surgical plans are changed for incidentaloma resection. Failure to identify synchronous colorectal carcinoma before surgery can lead to inadequate therapeutic procedures.